Morphological characterization of zinc oxide nanowires grown hydrothermally on PET substrate (Superficies y Vacío, 2014)
In this work, we report the synthesis and morphological characterization of ZnO nanowires grown on PET using a twostep process: (a) preparation of the seed layer, and (b) growth of the nanostructures. First step: solutions of zinc acetate dehydrate and 1-propanol of 10 mM concentration were spin coated on PET at 2000 rpm for 54 s using a syringe pump. Three of such cycles were carried out, between each cycle the layer was heating at 100°C in a furnace for 60 s. A seed layer was obtained after three layers of spin coating. Second step: vertical ZnO nanowires were grown by dipping the substrate in a 25 mM equimolar solution of zinc nitrate hexahydrate and hexamethylenetetramine. Afterwards, films were thermally treated with a commercial microwave oven at different power settings (350 and 700 W) for 5, 20 and 35 min. The ZnO nanowires obtained were characterized structural, optical and morphologically. Scanning electron microscopy analysis showed that the size of ZnO nanowires decreased in diameter when the heating time increased. XRD patterns show the presence of Zn(OH)2 overlapped with the ZnO phase. The ZnO nanowires bandgap energy was obtained from optical transmission spectra.